Dynamic melting in an open enclosure supported by a partial layer of metal foam: A fast thermal charging approach. (April 2023) - Ghalambaz, Mehdi; Aljaghtham, Mutabe; Chamkha, Ali J.; Abdullah, Abdelkader; Alqsair, Umar; Ghalambaz, Mohammad
Highlights: A shell-tube shape thermal energy storage unit with open inlet and outlet ports was studied. A stream of liquid PCM was allowed in the thermal energy storage unit. Liquid PCM can flow in the unit only after formation of a liquid film between the inlet and outlet. The flow of the liquid PCM in the enclosure notably promotes the melting and heat transfer rate. A full melting could be achieved in about 2.5 h for an 16-inch diameter enclosure. Abstract: A new design of fast charging latent heat thermal energy storage (dynamic melting) is proposed to further reduce the charging time. The proposed new design benefits from a stream of pressurized and heated liquid PCM entering and leaving the storage unit. Two layers of metal foam were also added to accelerate the thermal charging process further. The governing equations for the flow and heat transfer with phase change were introduced as partial differential equations and integrated using the finite element method. The impact of the porosity of foam layers, the foam ratio, and the geometrical placement of layers was investigated in the proposed design. The mounting location of a horizontal foam layer was not much important. Interestingly, it was found that a metal foam with high porosity produces a short thermal charging time. It was since the most important parameter in controlling the thermal charging time was forming a liquid PCM film between the inlet and outlet ports of the enclosure. Such as liquid film allows a passage for the pressurized and heated liquid PCM enters the enclosure and accelerates the melting process by a mixed convection mechanism. A full melting could be achieved in about 2.5 h in a 16-inch diameter enclosure.